Demand and Defective Growth Patterns: The Role of The Tradable and Non-Tradable Sectors in an Open Economy - Hlatshwayo, Sandile; Spence, Michael (American Economic Review, 2014)
This paper examines the underlying structural elements of US growth patterns, pre- and post-crisis. Prior to the recession, the US economy exhibited a defective growth pattern driven by outsized domestic demand. As domestic aggregate demand retreats to more sustainable levels relative to total income, the tradable side of the economy is a catalyst for restoring strong growth. A structural rebalancing is already underway; although it is only a third of the economy, the tradable sector generated more than half of gross gains in value-added since the start of the recovery. However, distributional issues loom on the horizon.